2022
DOI: 10.1097/xcs.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transfusion Volume and Transfusion Rate as Markers of Futility During Ultramassive Blood Transfusion in Trauma

Abstract: BACKGROUND: Using a large national database, we evaluated the relationship between RBC transfusion volume, RBC transfusion rate, and in-hospital mortality to explore the presence of a futility threshold in trauma patients receiving ultramassive blood transfusion. STUDY DESIGN: The ACS-TQIP 2013 to 2018 database was analyzed. Adult patients who received ultramassive blood transfusion (≥20 units of RBC/24 hours) were included. RBC transfusion volume and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 25 publications
1
38
2
Order By: Relevance
“…Loudon et al also reported that mortality increased with the number of units transfused in trauma patients. Their multivariate analysis showed that patients who received MT (>10 units RBC/4 hours) were 3 times 32 Gallastegi et al 13 reported slightly different findings, that it was not the absolute transfusion volume that was associated with increased mortality, but rather the transfusion rate, which had better discriminatory power for increasing mortality risk. The mean RBC transfusion rate calculated at 24 hours had a better ability to predict mortality (area under the receiver operating curve, 0.85 [95% CI, 0.84-0.86]), and the results showed that all patients with a final mean RBC transfusion rate of >7 units/h at 24 hours experienced in-hospital death.…”
Section: Umt Definitionmentioning
confidence: 98%
See 3 more Smart Citations
“…Loudon et al also reported that mortality increased with the number of units transfused in trauma patients. Their multivariate analysis showed that patients who received MT (>10 units RBC/4 hours) were 3 times 32 Gallastegi et al 13 reported slightly different findings, that it was not the absolute transfusion volume that was associated with increased mortality, but rather the transfusion rate, which had better discriminatory power for increasing mortality risk. The mean RBC transfusion rate calculated at 24 hours had a better ability to predict mortality (area under the receiver operating curve, 0.85 [95% CI, 0.84-0.86]), and the results showed that all patients with a final mean RBC transfusion rate of >7 units/h at 24 hours experienced in-hospital death.…”
Section: Umt Definitionmentioning
confidence: 98%
“…[2][3][4][5][6][7] Hospital implementation of MTPs is associated with reduced blood consumption, decreased incidence of multiorgan failure, and complications such as abdominal compartment syndrome, decreased hospital length of stay, overall cost, and mortality. [8][9][10][11][12] Ultra-MT (UMT), which may be defined as ≥20 units of RBC within 24 hours, 13,14 is increasingly being studied in trauma and surgical patients.…”
Section: Glossarymentioning
confidence: 99%
See 2 more Smart Citations
“…The timely cessation of futile resuscitation is essential for patient dignity and resource preservation. A recent article established a high discriminatory value for predicting early mortality in mean pRBC infusion rate at 24 h but not at 4 h among trauma patients who receive ultramassive transfusions [67 ▪ ]. Although this is applicable to intensivists, it is less so to trauma anaesthesiologists managing DCR.…”
Section: Use Of Biochemical Markers In Recognition Of Futilitymentioning
confidence: 99%